Estimating genotoxic effects of anticancer drugs using cytokinesis-block micronucleus assay on human lymphocytes - V. I. Minina; V. Yu. Buslaev (Фундаментальная и клиническая медицина)
Here we review the current experience of using cytokinesis-block micronucleus (CBMN) assay on cultures of human lymphocytes to evaluate genotoxic effects of anticancer drugs. Having performed search in PubMed, Scopus, Web of Science, TOXLINE, and the Cochrane Library, we identified a total of 172 relevant studies. Out of them, 89 were conducted in vitro, and 41 were published within the last decade. The mentioned studies concordantly demonstrated a significant increase in micronuclei, protrusions, nucleoplasmic bridges, and a decrease in proliferation in cells treated with anticancer drugs in a time- and dose-dependent manner. Notably, the results of CBMN assay are consistent with the data obtained from other cytogenetic techniques (comet assay, chromosomal aberration analysis, analysis of mutations in housekeeping genes, and fluorescence in situ hybridisation). Conclusion. CBMN assay permits a reliable evaluation of the mutagenic effects related to anticancer drugs.